2014
DOI: 10.2458/56.16917
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Problems in AMS 14C Dating of Fen Peat

Abstract: Four fen peat sequences in northern Finland were dated by the accelerator mass spectrometry (AMS) radiocarbon method in order to study past peatland dynamics and carbon accumulation patterns. Initially, plant macrofossils were used for dating. However, the dates were severely disordered, with marked inversions in all sequences. In one 140-cm peat core, for example, all ages fell within a ~1000-yr time window. Following these unreliable results, a few bulk peat samples were dated to help assess if any of the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…We do note, however, that Unit E contains MSA artifacts and therefore must be older than 40 ka. In order to fit the stratigraphy to the radiocarbon dates of Units B and C, Kuman and Clarke () introduced at the level of Unit D a long temporal gap, for which we do not see sedimentary evidence in terms of erosion, which should account for the much older age of Unit E. In addition, the presence of outliers among the 14 C dates, the possibility of contamination from roots of modern plants growing in the topsoil and the inherent difficulties in radiocarbon dating of peat (e.g., Shore, Bartley, & Harkness, ; Väliranta et al., ) indicate that great caution should be applied in the evaluation of the available data. For instance, Kuman and Clarke (, p. 110) dated Unit C to 12 ka, whereas Scott and Nyakale (, p. 500) dated underlying Unit D to 8 ka, in both cases using radiocarbon.…”
Section: Resultsmentioning
confidence: 99%
“…We do note, however, that Unit E contains MSA artifacts and therefore must be older than 40 ka. In order to fit the stratigraphy to the radiocarbon dates of Units B and C, Kuman and Clarke () introduced at the level of Unit D a long temporal gap, for which we do not see sedimentary evidence in terms of erosion, which should account for the much older age of Unit E. In addition, the presence of outliers among the 14 C dates, the possibility of contamination from roots of modern plants growing in the topsoil and the inherent difficulties in radiocarbon dating of peat (e.g., Shore, Bartley, & Harkness, ; Väliranta et al., ) indicate that great caution should be applied in the evaluation of the available data. For instance, Kuman and Clarke (, p. 110) dated Unit C to 12 ka, whereas Scott and Nyakale (, p. 500) dated underlying Unit D to 8 ka, in both cases using radiocarbon.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted, however, that age is not a very strong succession phase determinant; peatlands in Lapland had already initiated during the early Holocene period, but have remained as fens since mainly because of climate (e.g. Mäkilä and Moisanen, 2007; Väliranta et al, 2014). Climate envelope models suggest that temperature is the most important individual climate parameter to define the current distribution of bogs and fens (Parviainen and Luoto, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly young ages in the order of centuries or more have been previously reported in sedge peats Fig. 5 Pollen diagram showing select pollen types, NPPs, and microcharcoal data from Oukaïmeden plotted against core depth (cm) from temperate and high-latitude settings (Head et al 2007;Väliranta et al 2014). Similar problems may be occurring in the OUK case due to a combination of highly seasonal moisture regime and topogenous setting leading to sub-surface lateral groundwater flow through the deposit (promoting both mobility of humic acids as well as creating an attractive moisture reservoir for deeper rooting plants).…”
Section: Problematic Age Modelmentioning
confidence: 96%
“…Certainly, the problem of rootlet intrusion from overlying sediment will also be most critical in a sub-recent deposit due to the extremely high 14 C content of plant matter which formed in the second half of the 20th century, since the percentage of modern carbon (pMC) averaged 140 pMC over this interval and peaked at >190 pMC in the 1960s. Modest contributions of intrusive rootlets (<20% of the sample) could therefore result in apparent modern ages for samples of ~ 1,000 years age where 89 pMC is anticipated (Väliranta et al 2014); this appears the most likely explanation for reported values near 100 pMC at 68-69 cm, 52-53 cm, 40-41 cm, 38-39 cm, 34-35 cm, 32-33 cm and 26-27 cm depth (Table 3), all occurring within the rooting zone depth range of mid-to late 20th century plants. Similarly, high pMC values 20-21 cm and 14-15 cm depth may also reflect enrichment in 14 C of the dense upper root mat zone of plants which grew in the aftermath of 20th century bomb-testing (Hua et al 2013).…”
Section: Problematic Age Modelmentioning
confidence: 99%